Financiranje jedinica lokalne i područne (regionalne) samouprave - Šinković, Zoran (Array, 2019)
The territorial organization of modern states rests on the principles of decentralization, which includes the political, administrative and financial independence of the lower levels of government. It is a fundamental principle that no function, no job or task can be assigned to a certain level of government or body of government without the funds being provided. Local and regional selfgovernment are one of the most important areas of strategic importance for the development of democratic and quality public policies in the Republic of Croatia. The relationship between local and regional self-government and users can also be seen as a parallel process of strengthening the responsibility of local units for overall quality and «offering» public services in the local area. Therefore local and regional self-government have the right to various sources of funding in order to be able to carry out their tasks, or to provide, to a greater or lesser degree, better public services to their users.